Apatite geochemistry as a proxy for porphyry-skarn Cu genesis: a case study from the Sanjiang region of SW China - Liu, Qian; Pan, Li-Chuan; Wang, Xin-Song; Yan, Jun; Xing, Lang-Zhang (Frontiers in Earth Science, 2023)
In view of the importance of magmatic oxidation state and volatile composition (H2O-S-Cl) in porphyry Cu mineralzaition, exact identification of such magmatic information has been the basis of evaluating the Cu-mineralized potential of porphyries. Apatite, as a common accessory mineral in porphyry, is being recognized as an effective petrogenetic and metallogenic indicator. In this study, we analyzed the in-situ major and trace elements and Nd isotope of apatite from four granitic plutons in the Yidun terrane, SW China to provide new insights into identification of the magmatic features of Cu-mineralized pluton. The selected plutons include a Cu-mineralized (Hongshan), and three non-mineralized plutons (Cilincuo, Rongyicuo and Hagela). The chemical composition and textural observation indicate that the apatites analyzed are all of magmatic origin and have not been altered. Our result shows that apatite δCe value rather than δEu and Ga values are more valid indicator for magma oxidation state of the above four plutons. Based on apatite δCe values and zircon composition, the parental magma of the Hongshan pluton is identified as more oxidized than those of the other three plutons. Moreover, the higher Cl content (0.06–0.23 wt.%) in the Hongshan apatite than that in apatite from other three plutons (0.01–0.09 wt.%), indicates that the parental magma of the former pluton is more enriched in Cl. Apatite from the Hongshan pluton contains more SO3 (average 0.05 wt.%) than that from other three plutons (SO3 content mostly low than detection limit of EPMA), which may be related to higher magamtic oxygen fugacity of the Hongshan pluton. In addition, the Nd isotopic composition of apatite (εNd(t): -13.6–-5.9) demonstrates that the Cu-mineralized and non-mineralized plutons were derived from the melting of ancient lower crust. Furthermore, based on the geochemical signature of adakite revealed by apatite Sr/Y and δEu, the Hongshan pluton can be considered as the production of the partial melting of the thickened lower crust. Finally, an index system consisting of apatite δCe, Sr/Y and F/Cl is established to distinguish the Cu-mineralized and non-mineralized plutons.